1972
DOI: 10.1083/jcb.55.2.448
|View full text |Cite
|
Sign up to set email alerts
|

Development of Phenobarbital-Sensitive Control Mechanisms for Uridine Diphosphate Glucuronyltransferase Activity in Chick Embryo Liver

Abstract: Uridine diphosphate (UDP) glucuronyltransferase activity in chick liver rises at hatching from near zero to adult levels. This rise will occur prematurely in embryo liver during organ culture. Increase in enzyme activity during organ culture differs with embryo age: in liver from 11-day old embryos it ceases at adult values; in liver from 5-day old embryos it continues to much higher-than-adult levels. Phenobarbital added to culture medium accelerates these rises in enzyme activity and elevates the plateau rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…Maximal induction in the S16 preparation decreased after 12 DI to 4.76 nmol/min per mg at 17 DI and then increased to 7.71 nmol/min per mg by 20 DI. Similarly,, maximal induction in the microsomal preparations decreased after 14 DI to 8.06 nmol/min per mg at 18 DI and then increased sharply on subsequent days to a maximum of 15.13 nmol/min per mg at 1 day old, a value 9 times higher than 1-day-old controls,(also increased) and [30][31][32][33][34][35][36][37][38][39][40] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximal induction in the S16 preparation decreased after 12 DI to 4.76 nmol/min per mg at 17 DI and then increased to 7.71 nmol/min per mg by 20 DI. Similarly,, maximal induction in the microsomal preparations decreased after 14 DI to 8.06 nmol/min per mg at 18 DI and then increased sharply on subsequent days to a maximum of 15.13 nmol/min per mg at 1 day old, a value 9 times higher than 1-day-old controls,(also increased) and [30][31][32][33][34][35][36][37][38][39][40] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrastructural studies have shown that the hepatocytes are morphologically fully differentiated by 8 DI and that liver growth prior to 7 DI is due to cell growth and division whereas after 7 DI liver growth is almost solely due to cell division (31,32). One of the major changes in the hepatocytes from 4 to 7 DI is the proliferation of endoplasmic reticulum, and UDP-glucuronyltransferase activity is induced by phenobarbital in raft-cultured 7 DI embryonic liver, an agent that also induces a significant increase in endoplasmic reticulum (31,33 (34) investigated the development of phenobarbital-sensitive control mechanisms in cultured chicken embryo liver. They suggested that the differences in degree and time-course of induction of UDP-glucuronyltransferase in livers from 5-DI and 11-DI chicken embryos were a result of differences in regulatory mechanisms of enzyme induction at the two ages and that these differences reflected developmental changes occurring in ovo.…”
Section: Discussionmentioning
confidence: 99%
“…THe conclusion was that developmental onset of glucuronidation appears to be regulated by increased amounts of UDPGT (19,28). This idea was further reinforced by the ability of protein synthesis inhibitors to prevent the developmental onset of activity (29). However, the situation is complicated by the fact that yolk added to the tissue culture delays the development of glucuronyltransferase (19).…”
Section: Animalsmentioning
confidence: 99%
“…It also reduces or controls seizures or convulsions, except for absence (petit mal) seizures. Generic Phenobarbital oral elixir is available containing a high amount of alcohol which can increase possible unpleasant Effects 3,4 . Literature survey further revealed that the analytical method available for determination of drug phenobarbitone by modified conductometric analysis .…”
Section: Figure 1: Structure Of Phenobarbitonementioning
confidence: 99%